Conservation Analysis of Threatened Tree-Level Plant Species on the Island of Java - Aswangga Abigail Hidayat; Eni Suyantri; Yayan Wahyu Candra Kusuma (Journal of Biology, Environment, and Edu-Tourism, 2025)
Indonesia is one of the countries with the highest biodiversity in the world, with Java Island being one of the regions in Indonesia that has high biodiversity. This research provides a deeper understanding of the role of tree-level plants in maintaining the ecological balance of the forests on Java Island. The aim of this study is to analyze the number of endangered species on Java Island. The method used in this research is meta-analysis, utilizing secondary data from papers that have published their results. A total of 18 endangered species (VU, EN, CR) were identified. This study reveals a high plant diversity dominated by native species, yet there are 18 species that are threatened, requiring conservation efforts to maintain ecological balance and biological sustainability. Conservation becomes crucial in addressing the threats to biodiversity in Indonesia.